The Wedge - Laszlo Goerke (Institute for the Study of Labor (IZA), 1999)
It is often argued that the quantity which is traded on the market is independent of the side of the market which is taxed. However, this assertion need not hold, especially in imperfectly competitive markets like that for labour. Taking an efficiency wage economy as an example, it is shown that the legal incidence of social security contributions will affect the economic incidence if unemployment compensation is subject to social security contributions. Since this is the case in numerous OECD countries, the wedge between producer costs and the net wage might be an inappropriate device for measuring the impact of social security contributions on wages and employment.
Keywords: H22; J41; H55; 330; Efficiency wages; social security contributions; tax incidence; unemployment benefits; Lohnsteuer; Sozialversicherungsbeitrag; Steuerinzidenz; Steuerwirkung; Arbeitskosten; Arbeitsmarkttheorie; Effizienzlohn; Theorie